Surface properties of alginate/chitosan biofilm for wound healing application - Idris, M.I.; ADZHARI, M.F.; ABD. BAKIL, S.N.; Lee, T.C.; SELIMIN, M.A.; Abdullah, H.Z. (2020)
This work focuses on the fabrication of film based on natural iopolymers for wound healing application. Alginate and chitosan were choosen because of their oustanding properties such as biocompatible, hydrophilic and non-toxic. Earlier, the biopolymer film was fabricated by using alginate 1% wt and chitosan 1% wt. solutions at volume ratios of 99:1 and 97:3. Next, the biopolymer film solution was cross-linked with 1 M CaCl 2.2H2O for two hours and later dried for 24 hours at room temperature. Then, the surface properties of the prepared biopolymer films were characterised via Field Emission Scanning Electron Microscopy (FESEM), Atomic Force Microscopy (AFM) and contact angle measurement. It was observed that the surface of the biopolymer film became rougher as the volume of the chitosan increases. This condition was confirmed with average surface roughness, RA for biopolymer film with ratio of 97:3 resulted in higher values. Also, it was found that the surface of biopolymer films were hydrophilic after the contact angle was less than 90°. This can be concluded that the biopolymer based on alginate/chitosan is a promising candidate for wound healing materials particularly with good surface properties for faster healing process at the wound areas.